High-fructose corn syrup causes vascular dysfunction associated with metabolic disturbance in rats: Protective effect of resveratrol - Akar, Fatma; Uludag, Orhan; Aydin, Ali; Aytekin, Yasin Atacan; Elbeg, Sehri; Tuzcu, Mehmet; Şahin, Kazım (Pergamon-Elsevier Science Ltd, 2012)
High-fructose corn syrup (HFCS) is used in many prepared foods and soft drinks. However, limited data is available on the consequences of HFCS consumption on metabolic and cardiovascular functions. This study was, therefore, designed to assess whether HFCS drinking influences the endothelial and vascular function in association with metabolic disturbances in rats. Additionally, resveratrol was tested at challenge with HFCS. We investigated the effects of HFCS (10% and 20%) and resveratrol (50 mg/l) beverages on several metabolic parameters as well as endothelial relaxation, vascular contractions, expressions of endothelial nitric oxide synthase (eNOS), sirtuin 1 (SIRT1), gp91(phox) and p22(phox) proteins and superoxide generation in the aortas. Consumption of HFCS (20%) increased serum triglyceride, VLDL and insulin levels as well as blood pressure. Impaired relaxation to acetylcholine and intensified contractions to phenylephrine and angiotensin II were associated with decreased eNOS and SIRT1 whereas increased gp91(phox) and p22(phox) proteins, along with provoked superoxide production in the aortas from HFCS-treated rats. Resveratrol supplementation efficiently restored HFCS-induced deteriorations. Thus, intake of HFCS leads to vascular dysfunction by decreasing vasoprotective factors and provoking oxidative stress in association with metabolic disturbances. Resveratrol has a protective potential against the harmful consequences of HFCS consumption. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: High-fructose corn syrup; Resveratrol; Vascular dysfunction; Sirtuin; Nitric oxide; NADPH oxidase